From single MFC to cascade configuration: The relationship between size, hydraulic retention time and power density. (April 2016) - Walter, Xavier Alexis; Forbes, Samuel; Greenman, John; Ieropoulos, Ioannis A.
Highlights: Increased flow velocity of treated urine achieved equal power density as with fresh urine. A MFC cascade of decreasing size units achieved comparable absolute power as a cascade of equal size units. The volumetric footprint of a cascade stack was decreased by 50 % for a 25% increase in power density. Abstract: Achieving useful electrical power production with the MFC technology requires a plurality of units. Therefore, the main objective of much of the MFC research is to increase the power density of each unit. Collectives of MFCs will inherently include units grouped in cascades, whereby the outflow of one is the inflow to the next unit; such an approach allows for better fuel utilisation. However, such a configuration is subject to some important considerations, including: the size of the MFCs; the number of units i.e. the length of the cascade; hydraulic retention time; fuel quality; and optimisation of anode surface and microbial colonisation. In the present study, optimisation of the aforementioned aspects has been investigated in order to establish the most appropriate cascade design. Results demonstrate that an increased flow rate of treated urine achieved equal power density with the same setup when fed with fresh urine at a lower flow rate. The independent investigations of these parameters have led to the design of a cascade that maintains uniformity with regard to the aforementioned parameters, by incorporating units of decreasing size, thus allowing locally shorter hydraulic retention times and therefore leading to increased power density levels.